2016
DOI: 10.4187/respcare.04668
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-Flow Nasal Cannula Use on Neonatal Respiratory Support Patterns and Length of Stay

Abstract: HFNC introduction was significantly associated with a longer duration of mid-level respiratory support, decrease in oral feeding at discharge, increased retinopathy of prematurity rates, and higher use of intermediate care facilities, leading us to examine our noninvasive ventilation and weaning strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
3
13
2
1
Order By: Relevance
“…Although there are several studies that show HFNC to be similar to nasal CPAP, [7][8][9] in our own institution, we found a longer duration of respiratory support with the SEE THE ORIGINAL STUDY ON PAGE 1197 implementation of HFNC, 10 which has been echoed in other studies as well. 11,12 Despite the results of our study, HFNC continues to be frequently used given the aforementioned drawbacks to the current nasal CPAP interfaces.…”
supporting
confidence: 48%
“…Although there are several studies that show HFNC to be similar to nasal CPAP, [7][8][9] in our own institution, we found a longer duration of respiratory support with the SEE THE ORIGINAL STUDY ON PAGE 1197 implementation of HFNC, 10 which has been echoed in other studies as well. 11,12 Despite the results of our study, HFNC continues to be frequently used given the aforementioned drawbacks to the current nasal CPAP interfaces.…”
supporting
confidence: 48%
“…25 Another retrospective study by Hoffman et al of PBs <33 weeks GA found the HFNC group required a significantly longer duration of non-invasive respiratory support. 23 Shoemaker et al however reported no differences in CLD when retrospectively comparing PBs <30 weeks GA who received either CPAP or HFNC (35 vs. 31% respectively). 26 Previous research has shown that CPAP promotes the growth and development of premature lungs by maintaining recruitment of the infant's airway and parenchyma.…”
Section: Discussionmentioning
confidence: 96%
“…Another retrospective study by Hoffman et al . of PBs <33 weeks GA found the HFNC group required a significantly longer duration of non‐invasive respiratory support . Shoemaker et al .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several retrospective cohort studies have demonstrated a longer duration of respiratory support or supplemental oxygen therapy in very preterm infants managed with nHF compared with CPAP . The interpretation of these studies is limited by methodological considerations; there may be significant differences in the severity of lung disease and other comorbidities between the groups.…”
Section: Indications For Nhf Therapymentioning
confidence: 99%